The renewed Constitution through the eyes of the Youth - Muhlisaxon To’g’onboyeva (Periodica Journal, 2023)
This article examines the renewed Constitution of the Republic of Uzbekistan through the eyes of the young generation and its impact on promoting democracy, human rights, and the well-being of its citizens, particularly young people. The article provides an overview of the key changes introduced by the renewed Constitution, including the explicit recognition of ensuring human rights and freedoms as the highest goal of the state, the establishment of a strong parliament that enhances representation of diverse interests and perspectives of citizens, and the government's commitment to maintaining and developing relations with compatriots living abroad. The article also discusses the potential advantages of constitutional reforms for young people.
Keywords: Constitution; constitutional reform; New Uzbekistan